The Uralic-Yukaghir lexical correspondences: genetic inheritance, language contact or chance resemblance? - Aikio, Ante (Finnisch-Ugrische Forschungen, 2014)
The Uralic language family has often been hypothesized to be related to Yukaghir, even though no widely accepted evidence for this theory has been presented so far. The study of Uralic-Yukaghir relations has in part been held back by the scarcity of basic documentary and comparative work on the Yukaghir languages. The publication of A Historical Dictionary of Yukaghir (2006) by Irina Nikolaeva, however, has raised Yukaghir lexicology and historical phonology to a level that allows systematic comparison of Proto-Yukaghir and (Proto-)Uralic to be easily carried out. This paper discusses the lexical correspondences between Uralic and Yukaghir languages, and examines to what extent they can be explained as evidence of genetic relationship, products of language contact, or mere chance resemblances. It is argued that there is no clear lexical evidence supporting a genetic connection between the two families, and that no regular sound correspondences between the two proto-languages can be established. A majority of the Uralic-Yukaghir lexical comparisons suggested in earlier references seem to be chance resemblances, but a smaller corpus of probable loanwords supporting contacts between (Pre-)Proto-Samoyed and Proto-Yukaghir can be established.